Comparison of induction agents for rapid sequence intubation in refractory status epilepticus: A single-center retrospective analysis - Matthew R. Woodward; Adam Kardon; Jody Manners; Samantha Schleicher; Melissa B. Pergakis; Prajwal Ciryam; Jamie Podell; William Denney Zimmerman; Samuel M. Galvagno, Jr; Bilal Butt; Jennifer Pritchard; Gunjan Y. Parikh; et al. (Epilepsy & Behavior Reports, 2024)
Endotracheal intubation, frequently required during management of refractory status epilepticus (RSE), can be facilitated by anesthetic medications; however, their effectiveness for RSE control is unknown. We performed a single-center retrospective review of patients admitted to a neurocritical care unit (NCCU) who underwent in-hospital intubation during RSE management. Patients intubated with propofol, ketamine, or benzodiazepines, termed anti-seizure induction (ASI), were compared to patients who received etomidate induction (EI). The primary endpoint was clinical or electrographic seizures within 12 h post-intubation. We estimated the association of ASI on post-intubation seizure using logistic regression. A sub-group of patients undergoing electroencephalography during intubation was identified to evaluate the immediate effect of ASI on RSE. We screened 697 patients admitted to the NCCU for RSE and identified 148 intubated in-hospital (n = 90 ASI, n = 58 EI). There was no difference in post-intubation seizure (26 % (n = 23) ASI, 29 % (n = 17) EI) in the cohort, however, there was increased RSE resolution with ASI in 24 patients with electrographic RSE during intubation (ASI: 61 % (n = 11/18) vs EI: 0 % (n = 0/6), p =.016). While anti-seizure induction did not appear to affect post-intubation seizure occurrence overall, a sub-group of patients undergoing electroencephalography during intubation had a higher incidence of seizure cessation, suggesting potential benefit in an enriched population.